Relationship between gut microbiota and the pathogenesis of gestational diabetes mellitus: a systematic review - Ma, Sheng; Wang, Yuping; Ji, Xiaoxia; Dong, Sunjuan; Wang, Shengnan; Zhang, Shuo; Deng, Feiying; Chen, Jingxian; Lin, Benwei; Khan, Barkat Ali; Liu, Weiting; Hou, Kaijian (Frontiers in Cellular and Infection Microbiology, 2024)
Gestational diabetes mellitus (GDM) is a transient form of diabetes mellitus characterized by insulin resistance and pancreatic beta-cell dysfunction during pregnancy. In recent years, genome-wide association studies have revealed risk and susceptibility genes that confer genetic susceptibility to GDM. However, genetic susceptibility cannot explain the increased incidence of GDM worldwide, which is likely due to the increasing influence of environmental factors, particularly the gut microbiota. It was found that gut microbiota was closely related to the occurrence and development of GDM. Therefore, this paper reviews the relationship between gut microbiota and the pathogenesis of GDM to better understand the role of gut microbiota in GDM, and to provide a theoretical reference basis for the clinical application of gut microbiota in the treatment of related diseases.